Cellular technology: its psychosocial impact on young people - Raúl Jesús Rosales González (Medisur)
Cellular technology has literally revolutionized the world, it has changed the way to communicate and has facilitated the accessibility of people's exchanges. Young people, currently, are the ones who use this type of technology the most and, although there are many advantages of their use, they also bring with them negative effects such as excessive dependence on mobile phones, isolation or the inability to find alternatives resources for entertainment. The aim of this work is to reflect on the psychosocial effects that hyperdependence on cellular technology brings with it in young people.